Health nut : a feel-good cookbook - Damuck, Jess (Abrams, 2024)
"Emphasizing balance, recipe developer Jess Damuck shares more than 100 of her favorite easy, vegetable-centric dishes, which include just an occasional bit of meat, dairy, or decadence. Jess turns her considerable talent for creating gorgeous, obsession-worthy recipes to traditional health food--from smoothies to salads to grain bowls and tofu stir-fries--giving the genre a playful and delicious update, amping up the colors, textures, and flavors, and adding her own innovations that challenge our expectations about what health food can be. These recipes are perfect for a dinner party, but also doable for any busy weeknight"--Amazon.com.